2022
DOI: 10.1186/s43044-022-00274-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased RV:LV ratio on chest CT-angiogram in COVID-19 is a marker of adverse outcomes

Abstract: Background Right ventricular (RV) dilation has been used to predict adverse outcomes in acute pulmonary conditions. It has been used to categorize the severity of novel coronavirus infection (COVID-19) infection. Our study aimed to use chest CT-angiogram (CTA) to assess if increased RV dilation, quantified as an increased RV:LV (left ventricle) ratio, is associated with adverse outcomes in the COVID-19 infection, and if it occurs out of proportion to lung parenchymal disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the Suarez Castillejo et al ( 22 ) study, patients with COVID-19 and acute PE presented an elevated RV/LV ratio (mean at 1.0) without any association with ICU admission and mortality. In Tao et al ( 21 ) study, patients with adverse clinical events had a higher RV/LV ratio (1.06 ± 0.14 vs. 0.95 ± 0.15, p < 0.001). Moreover, the authors found that a cut-off value of 1.1 is a potential marker of adverse outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the Suarez Castillejo et al ( 22 ) study, patients with COVID-19 and acute PE presented an elevated RV/LV ratio (mean at 1.0) without any association with ICU admission and mortality. In Tao et al ( 21 ) study, patients with adverse clinical events had a higher RV/LV ratio (1.06 ± 0.14 vs. 0.95 ± 0.15, p < 0.001). Moreover, the authors found that a cut-off value of 1.1 is a potential marker of adverse outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…In the PE group ( n = 56/351, 16%), the mean RV/LV ratio was at 1.17 ( p = 0.011). In another study by Tao et al ( 21 ) CTPA was performed in 100 non-intubated COVID-19 patients without PE. The authors found a RV/LV ratio of 1.06 ± 0.14 in patients who developed adverse clinical events ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation